2011
DOI: 10.1029/2010jd014788
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of Arctic BrO measurements by chemical ionization mass spectrometry and long path-differential optical absorption spectroscopy

Abstract: [1] A measurement intensive was carried out in Barrow, Alaska, in spring 2009 as part of the Ocean-Atmosphere-Sea-Ice-Snowpack (OASIS) program. The central focus of this campaign was the role of halogen chemistry in the Arctic. A chemical ionization mass spectrometer (CIMS) performed in situ bromine oxide (BrO) measurements. In addition, a long path-differential optical absorption spectrometer (LP-DOAS) measured the average concentration of BrO along light paths of either 7.2 or 2.1 km. A comparison of the 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
215
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 120 publications
(223 citation statements)
references
References 80 publications
8
215
0
Order By: Relevance
“…Recently, novel observations of BrO (Liao et al, 2011) have shown that "BrO clouds" tend to be distributed homogeneously over scales of a few kilometres during ODEs, while Salawitch et al (2010) found that BrO columns are correlated with the height of the tropopause, although some "hotspots" are related to free-tropospheric or stratospheric intrusions.…”
Section: P S Monks Et Al: Tropospheric Ozone and Its Precursorsmentioning
confidence: 99%
“…Recently, novel observations of BrO (Liao et al, 2011) have shown that "BrO clouds" tend to be distributed homogeneously over scales of a few kilometres during ODEs, while Salawitch et al (2010) found that BrO columns are correlated with the height of the tropopause, although some "hotspots" are related to free-tropospheric or stratospheric intrusions.…”
Section: P S Monks Et Al: Tropospheric Ozone and Its Precursorsmentioning
confidence: 99%
“…Depending on meteorological conditions, spectra were recorded with integration times ranging between 1 and 50 s. The LP-DOAS light paths were almost parallel to the coast and are therefore are used to represent the same air mass. Liao et al (2011) concluded that BrO is often distributed homogeneously on spatial scales of up to at least 4 km. Since the measurements from the LP-DOAS were collected within this distance, they are considered representative at the OOTI site.…”
Section: Bromine Monoxidementioning
confidence: 99%
“…The BrO measurements described in this paper were collected with a long-path DOAS (LP-DOAS) instrument (Platt and Stutz, 2008). The general set-up used in this study is described elsewhere (Frieß et al, 2011;Liao et al, 2011). The LP-DOAS telescope was located approximately 1 km inland on a building facing northwest.…”
Section: Bromine Monoxidementioning
confidence: 99%
“…The inorganic halogen species Br 2 , Cl 2 , BrO, and HOBr were measured in situ at a height of ∼ 1.5 m above the snowpack with a chemical ionization mass spectrometer (CIMS) employing I − ion chemistry. This method, as used in Barrow, and these observations have been published in Liao et al (2011Liao et al ( , 2012Liao et al ( , 2014. ClO was measured at a height of ∼ 3 m above the snowpack via chemical conversion to a stable, halogenated product followed by online separation and detection by gas chromatography with electron capture detection hyde (HCHO) concentrations were measured at 1 Hz frequency from the fixed tower using a tunable diode laser absorption spectrometer as described in Fried et al (1997) and Lancaster et al (2000).…”
Section: R Thompson Et Al: Interactions Of Bromine Chlorine Anmentioning
confidence: 99%